Green Hospital Initiative by a North Delhi Tertiary Care Hospital: Current Scenario and Future Prospects - Tanisha Bharara; Renu Gur; Shalini Dewan Duggal; Pragnya Jena; Shilpa Khatri; Pradeep Sharma (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Climate change is likely to affect all forms of life. Healthcare professionals and planners are gearing up to shoulder responsibility to mitigate climate change. The present study was undertaken to explore the journey of our hospital towards becoming a climate friendly green hospital. Aim: To study the progress made by our institute towards becoming a climate friendly green hospital based on seven directives of World Health Organization’s (WHO) discussion draft on climate change. Materials and Methods: A retrospective observational study was conducted from January 2013 to December 2017 by the Departments of Biomedical Waste management (BMW) and Public Works Deprtment (PWD) to analyse hospital’s journey towards becoming a green hospital. The observation was made in line with the 7 WHO directives related to climate change and compared over the years. Results: It was observed that in the past five years there have been several initiatives taken by the hospital with intent to improve energy efficiency like replacement of halogens and Compact Fluorescent Lamps (CFL) with Light Emitting Diodes (LED), diesel with Compressed Natural Gas (CNG) as fuel for boiler in laundry. For conservation and effective utilisation of resources, solar water heating system and seven rain water harvesting systems have been installed. Efforts have been made towards waste minimisation and efficient management with a sewage treatment plant for management of liquid waste and BMW management and recycling as per the guidelines. Conclusion: Over the years we have taken several steps towards becoming a climate friendly green hospital. This study emphasises our commitment towards a healthy environment for the wellbeing of our patients.